EFEKTIVITAS PENGGUNAAN STRATEGI THE POWER OF TWO DALAM MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VIII DI SEKOLAH MENENGAH PERTAMA ISLAM NURUL ULUM MANGAR TLANAKAN PAMEKASAN - Rohmaniyah, Faizatur; Subhan, Moh (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2024)
The power of two strategies is a learning activity to encourage learning and strengthen the importance and synergy of two people with the principle that thinking together is better than thinking alone, this will be very effective if the teacher conditions students to be active and there is a dynamic and mutually supportive relationship between one student with another. This research uses a qualitative approach. Data sources were obtained through observation, interviews, and documentation. The informants were the principal, PAI teachers, and students. The results of this research show that the implementation of the power of two learning strategies shows that the teaching and learning process at Nurul Ulum Islamic Middle School is running actively. Second, the supporting factor in improving student learning achievement at Islan Nurul Ulum Middle School is the extensive experience and knowledge possessed by the teacher which will certainly make it easier for students to receive lessons in small groups of 2 people by the teaching teacher. The inhibiting factor is that students do not pay attention to the teacher when explaining the lesson and students are often silent during discussions. The implications of this research include 1) Implementation of More Effective Learning Strategies, 2) Developing Teacher Capacity, 3) Collaboration between Students, 4) Increasing Student Involvement, 5) Development of Formative Assessment.